Implementation and Effects of the Synthetic Analytical Structural Method Improving Writing Skills in Muslim School - Delfitraweri, Delfitraweri; Melindawati, Silfi; Satrial, Ardi; Dahliana, Dina; Rahmatika, Nada; Yolanda, Sylvi Aulia; Cahyani, Rahmi Indah (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Students' success in becoming proficient in writing is determined by the teacher's use of appropriate methods. Teachers should have various method choices in the learning process so that students can easily understand the subject matter. This research aims to analyze the effects of using synthetic analytical structural methods in teaching writing for elementary schools in muslim school. The researcher used the participant type classroom action research method as a research method, data sources were taken from twenty participants using pre-test daily student values, questionnaires and direct observation of researchers at all stages of the research, all participants were selected using a simple random sampling technique. All data were analyzed using SPSS 21 software with descriptive analysis. Overall, the teacher stated that the implementation of the synthetic analytical structural method went well in the process of learning writing material. Furthermore, data analysis of learning outcome scores shows that the synthetic analytical structural method can improve students' writing abilities. This increase in ability can be seen from the cumulative scores of the first and second cycles with the pre-test score which was previously at 66.67% increasing to 83.33%. This means that the synthetic analytical structural method can actually be used as a solution as an effective method for educating students to be proficient in writing.